Genome Sequence of the Streptomycin-Producing Microorganism Streptomyces griseus IFO 13350 - Ohnishi, Yasuo (American Society for Microbiology (ASM), 2008)
We determined the complete genome sequence of Streptomyces griseus IFO 13350, a soil bacterium producing an antituberculosis agent, streptomycin, which is the first aminoglycoside antibiotic, discovered more than 60 years ago. The linear chromosome consists of 8,545,929 base pairs (bp), with an average G+C content of 72.2%, predicting 7,138 open reading frames, six rRNA operons (16S-23S-5S), and 66 tRNA genes. It contains extremely long terminal inverted repeats (TIRs) of 132,910 bp each. The telomere's nucleotide sequence and secondary structure, consisting of several palindromes with a loop sequence of 5′-GGA-3′, are different from those of typical telomeres conserved among other Streptomyces species. In accordance with the difference, the chromosome has pseudogenes for a conserved terminal protein (Tpg) and a telomere-associated protein (Tap), and a novel pair of Tpg and Tap proteins is instead encoded by the TIRs. Comparisons with the genomes of two related species, Streptomyces coelicolor A3(2) and Streptomyces avermitilis, clarified not only the characteristics of the S. griseus genome but also the existence of 24 Streptomyces-specific proteins. The S. griseus genome contains 34 gene clusters or genes for the biosynthesis of known or unknown secondary metabolites. Transcriptome analysis using a DNA microarray showed that at least four of these clusters, in addition to the streptomycin biosynthesis gene cluster, were activated directly or indirectly by AdpA, which is a central transcriptional activator for secondary metabolism and morphogenesis in the A-factor (a γ-butyrolactone signaling molecule) regulatory cascade in S. griseus.